Industry influence on mental health research: depression as a case example - Cosgrove, Lisa; Patterson, Elissa H.; Bursztajn, Harold J. (Frontiers in Medicine, 2024)
Emotional distress has been rising since before the COVID-19 pandemic and the public is told that depression is a major public health problem. For example, in 2017 depressive disorders were ranked as the third leading cause of 'years lost to disability' and the World Health Organization now ranks depression as the single largest contributor to global disability. Although critical appraisals of the epidemiological data raise questions about the accuracy of population-based depression estimates, the dominance of the medical model and the marketing of psychotropics as "magic bullets," have contributed to a dramatic rise in the prescription of psychiatric drugs. Unfortunately, the pharmaceutical industry's influence on psychiatric research and practice has resulted in overestimates of the effectiveness of psychotropic medications and an under-reporting of harms. This is because the principles that govern commercial entities are incongruent with the principles that guide public health research and interventions. In order to conduct mental health research and develop interventions that are in the public's best interest, we need non-reductionist epistemological and empirical approaches. that incorporate a biopsychosocial perspective. Taking depression as a case example, we argue that the socio-political factors associated with emotional distress must be identified and addressed. We describe the harms of industry influence on mental health research and show how the emphasis on 'scaling up' the diagnosis and treatment of depression is an insufficient response from a public health perspective. Solutions for reform are offered.